Three‐year outcome of directional atherectomy and drug coated balloon for the treatment of common femoral artery steno‐occlusive lesions. Issue 4 (14th November 2021) - Cioppa, Angelo; Franzese, Michele; Gerardi, Donato; Pucciarelli, Armando; Popusoi, Grigore; Stabile, Eugenio; Salemme, Luigi; Sada, Lidia; Verdoliva, Sebastiano; Burattini, Osvaldo; Fimiani, Luigi; Ferrone, Marco; et al.
Abstract: Background: Endarterectomy is considered the gold standard therapy for common femoral artery (CFA) steno‐occlusive lesions, but a significant risk of perioperative mortality and complications has been reported. Objective: Aim of this study is to evaluate the efficacy at a long‐term follow‐up of patients with CFA steno‐occlusive lesions treated with directional atherectomy and drug coated balloon (DCB). Material and methods: In this single‐center registry, 78 patients (male: 80.7%; age: 71 ± 15 years; occlusions: 25%) with 80 CFA lesions were included, with 39.7% of them undergoing directional atherectomy and drug coated balloon due to critical limb ischemia and 60.3% due to lower‐limb intermittent claudication. The long‐term follow‐up was completed by 75 patients (3 years). The 31 patients with critical ischemia (39.7%) were further subdivided into 20 (25.6%) patients with pain at rest and 11 (14.1%) with trophic changes, ulcers and/or tissue loss. We considered the primary and the secondary outcome, referring, respectively to peak systolic velocity ratio (PSVR) ≥ 2.4 on duplex or > 50% stenosis on digital subtraction angiography at 36 months and to clinically driven target lesion revascularization at 36 months. Results: The primary and secondary outcome was obtained in 84% and 86.7% of patients, at 36 months of follow up. Bailout stenting was necessary in 6/80 cases (7.5%) for suboptimal result. Freedom from MALE was obtained in 98.6% of patients. Conclusions: These results confirm that directional atherectomy and drug coated balloon strategy for the treatment of CFA lesions is effective at a long‐term follow‐up and could be considered as a good alternative to surgery.